Price estimation and visual evaluation of actual white fabrics used for dress shirts and their photographic images - Maruyama Tomoya; Kim KyoungOk; Takatera Masayuki (AUTEX Research Journal)
Consumers recognize the appearance and texture of fabric through viewing photographic images on E-commerce. However, the relationship between evaluations of the actual fabric and its image remains unclear. To understand the evaluation difference between actual fabric and its image, we investigated the relationship of visual evaluations including the price evaluation between actual white fabrics used for dress shirts and their photographic images concerning the online purchase of items presented by their photos. Participants evaluated the impressions of 24 white fabrics (actual fabrics and their images), comparing them with a standard white fabric. Participants also estimated the prices of shirts hypothetically made from different fabrics. We compared the difference between the results for actual fabrics and images. We also carried out a principal component analysis of those impressions and examined the relationship among principal component analysis results, weave structure, and fabric materials and price estimation. In a comparison of actual fabric and image evaluations, the impression of glossiness and brightness differed, with the actual fabrics being rated significantly higher in terms of glossiness and brightness. These differences are due to the difference in media (i.e., direct viewing versus screen display), although the visual environment of the lighting and displays may have had an effect. In principal component analysis, the first principal components were Delicateness and Glossiness for both actual fabrics and their images. The second principal components were Lightness and Coolness for the images of fabrics and Lightness, Coolness, and Softness for the actual fabrics. Fabrics evaluated highly in the first principal component had high price estimations. Thus, it is clear that Delicateness and Glossiness affected the price evaluation for both actual white fabrics and their images. Fabrics with a high value of Delicateness and Glossiness were a poplin made of at least 95% cotton. In contrast, fabrics containing linen and having a small repeating dobby pattern with roughness were evaluated as having low Delicateness and Glossiness and were assessed at a lower price. Additionally, even in the case of blended fabrics such as a cotton–polyester fabric, the expected price was high for diagonal patterns such as stripes and checks. These results will be helpful in the procurement of fabrics with which to make clothing and in the marketing of clothing for E-commerce.